Optimized Equipment Lubrication Conventional Lube, Oil Mist Technology and Full Standby Protection - Bloch, Heinz P. 1933- (De Gruyter, 2022)
The book describes the methods and procedures to optimally applying lubricant to all kinds of general purpose machines. These include process pumps, electric motors and other equipment incorporating rolling element bearing where traditional methods are usually very much out of step with best available practices. Failure analysis, reliability strategies, remedial steps or desirable substitute approaches are also explained.